Does the aggressiveness of the prey modify the attack behavior of the predator Supputius cincticeps (Stål) (Hemiptera, Pentatomidae)? - Silva, Rafael Braga da; Corrêa, Alberto Soares; Lucia, Terezinha Maria Castro Della; Pereira, Alexandre Igor Azevedo; Cruz, Ivan; Zanuncio, José Cola (Revista Brasileira de Entomologia, 2012)
Does the aggressiveness of the prey modify the attack behavior of the predator Supputius cincticeps (Stål) (Hemiptera, Pentatomidae)? The stink bug Supputius cincticeps (Stål) (Hemiptera, Pentatomidae) is a predator found in several Brazilian regions, which possesses desirable attributes as a natural control agent and in biological control programs. The aim of this study was to test if the attack behavior and predation success of S. cincticeps were affected by prey species. Larvae of Tenebrio molitor (L.) (Coleoptera, Tenebrionidae), Spodoptera frugiperda (J. E. Smith) (Lepidoptera, Noctuidae), and Thyrinteina arnobia (Stoll) (Lepidoptera, Geometridae) were offered to S. cincticeps in laboratory bioassays where predatory attack and prey defensive behaviors were observed for 2-hour periods. The attack behavior of S. cincticeps changed with the prey species offered. More than 25% of T. molitor and S. frugiperda larvae were immediately attacked, but T. arnobia was not immediately attacked by S. cincticeps. Successful attack (i.e., successful insertion of the predator stylets into the prey) depends on the region of the body attacked, with a greater proportion of successful attacks in the anterior than in the median or posterior regions. Larvae of T. arnobia and S. frugiperda displayed a sequence of abrupt head and body movements in response to S. cincticeps attack. Attempts of predation were more successful on T. molitor and S. frugiperda than on T. arnobia. Information about the differential attack behavior of S. cincticeps on different prey species is important for designing successful biological control programs using this hemipteran predator.

A agressividade da presa altera o comportamento de ataque do predador Supputius cincticeps (Stål) (Hemiptera, Pentatomidae)? O percevejo Supputius cincticeps (Stål) (Hemiptera, Pentatomidae) é um predador encontrado em várias regiões brasileiras, que possui atributos desejáveis como agente de controle natural ou em programas de controle biológico. O objetivo deste trabalho foi testar se diferentes espécies de presa podem afetar o comportamento de ataque e o sucesso de predação de S. cincticeps. Larvas de Tenebrio molitor (L.) (Coleoptera, Tenebrionidae), Spodoptera frugiperda (J. E. Smith) (Lepidoptera, Noctuidae) e Thyrinteina arnobia (Stoll) (Lepidoptera, Geometridae) foram oferecidas a S. cincticeps, em bioensaios de laboratório, onde o comportamento de ataque do predador e o comportamento de defesa das presas foram observados por período de duas horas. O comportamento de ataque de S. cincticeps às presas apresentou variações nas frequências dos atos predatórios. O sucesso da inserção dos estiletes na presa depende da parte do corpo que é atacada (anterior, mediana ou posterior), apresentando maior sucesso quando o ataque ocorre na região anterior. As larvas de T. arnobia e S. frugiperda apresentaram maior frequência de movimentos bruscos quando atacadas por S. cincticeps, enquanto as de T. molitor não exibiram tais reações. Consequentemente, o sucesso da predação de S. cincticeps foi maior sobre T. molitor e S. frugiperda e consideravelmente menor em T. arnobia. Essas informações sobre as diferenças no comportamento de ataque de S. cincticeps a diferentes presas são úteis para os programas de controle biológico envolvendo hemípteros predadores.
Keywords: Biological control; Ethogram of predation; Fall armyworm; Stink bug predator